Induced pluripotent stem cells as a new getaway for bone tissue engineering: A systematic review. (1st December 2016) - Bastami, Farshid; Nazeman, Pantea; Moslemi, Hamidreza; Rezai Rad, Maryam; Sharifi, Kazem; Khojasteh, Arash
Abstract: Objectives: Mesenchymal stem cells (MSCs) are frequently used for bone regeneration, however, they are limited in quantity. Moreover, their proliferation and differentiation capabilities reduce during cell culture expansion. Potential application of induced pluripotent stem cells (iPSCs) has been reported as a promising alternative source for bone regeneration. This study aimed to systematically review the available literature on osteogenic potential of iPSCs and to discuss methods applied to enhance their osteogenic potential. Methods and materials: A thorough search of MEDLINE database was performed from January 2006 to September 2016, limited to English‐language articles. All in vitro and in vivo studies on application of iPSCs in bone regeneration were included. Results: The current review is organized according to the PRISMA statement. Studies were categorized according to three different approaches used for osteo‐induction of iPSCs. Data are summarized and reported according to the following variables: types of study, cell sources used for iPSC generation, applied reprogramming methods, applied osteo‐induction methods and treatment groups. Conclusion: According to the articles reviewed, osteo‐induced iPSCs revealed osteogenic capability equal to or superior than MSCs; cell sources do not significantly affect osteogenic potential of iPSCs; addition of resveratrol to the osteogenic medium (OM) and irradiatiation after osteogenic induction reduce teratoma formation in animal models; transfection with lentiviral bone morphogenetic protein 2 results in higher mineralization compared to osteo‐induction in OM; addition of TGF‐β, IGF‐1 and FGF‐β to OM increases osteogenic capability of iPSCs.